2022
DOI: 10.1177/10499091221102581
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nutritional Index in Patients With End-Stage Oral Cancer

Abstract: Purpose As the incidence of oral cancers is on the rise, we aimed to evaluate the usefulness of the prognostic nutritional index (PNI) as a predictor of survival in patients with terminal oral cancer. Methods We evaluated the association between laboratory and PNI values and survival days in 33 patients who died of oral cancer between 2004 and 2019 ,excluding 4 patients who underwent gastric banding out of 39with gastric banding. The observation period was from the date of palliative care recommendation to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Survival analysis revealed that the three scoring systems can show good prediction efficiency. PNI, an index related to ALB concentration and lymphocyte count, has been used to predict the risk of postoperative complications and the OS of patients with GC and other cancers[ 24 , 41 , 42 ]. The CONUT score is an index related to ALB concentration, lymphocyte count, and TC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis revealed that the three scoring systems can show good prediction efficiency. PNI, an index related to ALB concentration and lymphocyte count, has been used to predict the risk of postoperative complications and the OS of patients with GC and other cancers[ 24 , 41 , 42 ]. The CONUT score is an index related to ALB concentration, lymphocyte count, and TC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 is consistent with the original CONUT scoring system in the literature [ 40 ]. Compared to other nutritional tools and parameters, such as the Glasgow prognostic score (GPS), modified GPS [ 41 , 42 ], PNI [ 43 , 44 ], AGR [ 45 , 46 ], systemic immune inflammation index [ 47–50 ], GNRI [ 51–53 ], and CAR [ 40 , 54 , 55 ], CONUT has the following advantages. First, CONUT is a standardized scoring system with clear scoring criteria ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…a. The PNI and SII before treatment were compared between the two groups, PNI = 5× lymphocyte count (×10 9 /L) + serum albumin (g/L), and SII = peripheral platelet count (×10 9 /L) * peripheral neutrophil count (×10 9 /L)/peripheral lymphocyte count (×10 9 /L), where PNI refers to the prognostic nutritional index [15], and SII to the systemic immune-inflammation index [17]. PNI≥50 indicates a normal nutritional status, and PNI<50 indicates malnutrition, while there is no commonly agreed normal level for SII.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Studies have established an association between PNI and the prognosis of various malignant tumors. Patients with oral cancer or gastric cancer who had a low PNI tended to have a poorer prognosis, resulting in reduced overall survival time [15,16]. The systemic immune-inflammation index (SII) can reflect both local and systemic reactions in the body.…”
Section: Introductionmentioning
confidence: 99%